Mathematical Justification Research in Mathematics Education Across Grades: A Systematic Literature Review - Surya Kurniawan; Rizky Rosjanuardi; Aswin Aswin (Hipotenusa : Journal of Mathematical Society, 2022)
Justification is a set of responses or responses that a person gives when asked to provide mathematical reasons for the results he makes. Justification can be used as a social process in which mathematical knowledge is explained, and systematically verified based on ideas, definitions, and properties that apply in mathematics such as representations used to display concepts. Research on justification in mathematics education has been carried out for a long time. This study aims to evaluate mathematics justification studies from articles published after 2016 and before April 2022 from ERIC and Google Scholar Databases. The key questions in this study are how these articles are distributed based on year publication, country, participant, mathematics subject, method, and how to support mathematical justification. This study used a Systematic Literature Review (SLR) by Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines including inclusion and exclusion criteria and then the data were extracted, resulting in 30 studies to be reviewed. The result shows that by year of publication the articles fluctuation distributed, based on country no data from Africa and Australia was found in the databases, the participant is mostly preservice mathematics teachers, whereas only one publication studied in high school students, geometry is the most mathematics subject used in research since every grade contain this material, the method is frequently given by qualitative research with various approach, how to supporting mathematical justification is also discussed.